Eigenvalue distribution of diluted random matrix ensemble with correlated entries appearing in the random graphs theory - Vengerovsky, V. V. (Журнал математичної фізики, аналізу, геометрії, 2005)
Existing of weak limit in probability of counting measures of some ensemble of the diluted random matrices is proved. The Stiltjes transform of limiting measure is expressed by the function. This function is unique solution of the functional equation. Mathematics Subject Classification: 60B10, 60H30.